Cystic medial necrosis: pathological findings and clinical implications - Yuan,Shi-Min (2011)
Cystic medial necrosis (CMN) is a disorder of large arteries, in particular the aorta, characterized by an accumulation of basophilic ground substance in the media with cyst-like lesions. CMN is known to occur in certain connective tissue diseases such as Marfan syndrome, Ehlers-Danlos syndrome, and annuloaortic ectasia, which usually result from degenerative changes in the aortic wall. The relationships between CMN and congenital heart defects as well as other disorders have been evidenced. The mechanisms are still controversial, even though many molecular studies have been conducted. The aim of the present article is to provide a comprehensive overview of the CMN lesion in terms of pathologic features, clinical implications and etiologies based on molecular research results.